2017
DOI: 10.1002/pd.5135
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal influence of congenital heart defects on trajectories of cortical folding of the fetal brain using three‐dimensional ultrasound

Abstract: Fetal cortical folding can be evaluated reliably by measuring brain fissure depths. Trajectories of cortical folding between 22 and 32 weeks' GA seem to be influenced by CHD. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 46 publications
1
24
3
Order By: Relevance
“…Thus, the used methodology in this study is capable of determining the extent of the delay, which was demonstrated to be small (3 days). Moreover, we do not see a difference in the slopes of the development between CHD and control cases, indicating no further delay in the cortical growth trajectory in the third trimester, as described by other authors . A possible explanation for this absence of third trimester difference might be that the role of fetal brain oxygenation is being magnified in the literature due to case selection.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Thus, the used methodology in this study is capable of determining the extent of the delay, which was demonstrated to be small (3 days). Moreover, we do not see a difference in the slopes of the development between CHD and control cases, indicating no further delay in the cortical growth trajectory in the third trimester, as described by other authors . A possible explanation for this absence of third trimester difference might be that the role of fetal brain oxygenation is being magnified in the literature due to case selection.…”
Section: Discussionsupporting
confidence: 72%
“…Cortical maturation by measuring fissure depth has been described before using both MRI and US in non‐CHD fetuses.Application of these techniques shows significant differences in the depth of the POF and calcarine fissure in CHD cases as compared with controls . These fissures were also reported to be shallower in CHD neonates than in controls with a comparable GA, which was explained as delayed maturation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, fetuses with CHD have higher serum s‐Flt and soluble Endoglin levels as well as increased s‐Flt in the frontal cortex and the basal ganglia of the brain . The combination of suboptimal perfusion with an anti‐angiogenic milieu results in alterations in structural brain development in utero, especially in the third trimester . The accumulation of data showing abnormal neurodevelopment in fetuses with hypoplastic left heart triggered the International Society for Ultrasound in Obstetrics and Gynecology to release a position statement in 2017 encouraging caregivers to discuss these prenatal findings with expecting couples and to warn them of the potential impact they may have on long‐term developmental outcomes …”
Section: Advances In Diagnosis and Treatment Of Fetal Cardiac Anomaliesmentioning
confidence: 99%